2005
DOI: 10.1523/jneurosci.0148-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Synaptic Enhancement with Acute Intermittent Hypoxia Improves Respiratory Function after Chronic Cervical Spinal Cord Injury

Abstract: Respiratory insufficiency is the leading cause of death after high-cervical spinal cord injuries (SCIs). Although respiratory motor recovery can occur with time after injury, the magnitude of spontaneous recovery is limited. We hypothesized that partial respiratory motor recovery after chronic cervical SCI could be strengthened using a known stimulus for spinal synaptic enhancement, intermittent hypoxia. Phrenic motor output was recorded before and after intermittent hypoxia from anesthetized, vagotomized, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
225
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 190 publications
(245 citation statements)
references
References 50 publications
15
225
5
Order By: Relevance
“…These results conform to the hypothesis that endogenous "self-repair" mechanisms associated with the sCPP can impact breathing in the awake, freely behaving rat after chronic C2HS. It should be mentioned, however, that our hypoxia data contrast with prior reports (Golder and Mitchell, 2005;Fuller et al, 2006), but this appears to be due to different approaches employed. For example, Golder and Mitchell (2005) found that the IL phrenic hypoxic response did not change 2-8-week post-C2HS.…”
Section: Re-emergence Of Ipsilateral Phrenic Motoneuron Activitycontrasting
confidence: 97%
See 4 more Smart Citations
“…These results conform to the hypothesis that endogenous "self-repair" mechanisms associated with the sCPP can impact breathing in the awake, freely behaving rat after chronic C2HS. It should be mentioned, however, that our hypoxia data contrast with prior reports (Golder and Mitchell, 2005;Fuller et al, 2006), but this appears to be due to different approaches employed. For example, Golder and Mitchell (2005) found that the IL phrenic hypoxic response did not change 2-8-week post-C2HS.…”
Section: Re-emergence Of Ipsilateral Phrenic Motoneuron Activitycontrasting
confidence: 97%
“…It should be mentioned, however, that our hypoxia data contrast with prior reports (Golder and Mitchell, 2005;Fuller et al, 2006), but this appears to be due to different approaches employed. For example, Golder and Mitchell (2005) found that the IL phrenic hypoxic response did not change 2-8-week post-C2HS. In that study, the hypoxic response was expressed relative to IL phrenic activity during a subsequent hypercapnic challenge.…”
Section: Re-emergence Of Ipsilateral Phrenic Motoneuron Activitycontrasting
confidence: 97%
See 3 more Smart Citations